Sindicatos campesinos y poder estatal en la Bolivia evista (2005-2010) - Bruno Fornillo; Marcos Schiavi (Les Cahiers ALHIM)
In Bolivia, the arrival of the State in 2005 by the Movement Towards Socialism led to inquire if we were in the presence of a government of social movements. Of course, the passage established by the process « evista » led to the emergence of new questions, marked throughout by the evidence that social organizations have gone from « political ground » to the state government arena. To probe the possible answers on how they perform on stage novel tackles our work. To account for a picture that helps illustrate the nature of the coalition government, open the lens to the institutions of power subordinate in order to characterize the presence of social leaders in national power and decisional logic MAS government. In a first part we analize the presence of leaders of social organizations in the government, in addition to focusing on new institutional of executive power that were designed to accommodate them (pay attention to the composition and evolution of the Constituent Assembly, the legislature, ministry, etc.). Then we move into the dynamics acquired « instrumento político » once Evo Morales became president, prisoner of a change of proportions, as passed to function in the « political underground » to become the new party in government function. Finally, we present the system and the type of decisions internal articulation of the different sectors of the new power block. The main assumption that underlies the article is that this is the incorporation of the democratic system of settling disputes of Bolivian unions to the State.